If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 + 5 + 2 = 3 + 2 + 2x Reorder the terms: 4 + 5 + 2 + x = 3 + 2 + 2x Combine like terms: 4 + 5 = 9 9 + 2 + x = 3 + 2 + 2x Combine like terms: 9 + 2 = 11 11 + x = 3 + 2 + 2x Combine like terms: 3 + 2 = 5 11 + x = 5 + 2x Solving 11 + x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 11 + x + -2x = 5 + 2x + -2x Combine like terms: x + -2x = -1x 11 + -1x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 11 + -1x = 5 + 0 11 + -1x = 5 Add '-11' to each side of the equation. 11 + -11 + -1x = 5 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 5 + -11 -1x = 5 + -11 Combine like terms: 5 + -11 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 | | 51-81.623= | | 0=(.25x^4)-(2x^2)-1 | | 7.2g+1.5=6+3.2g | | 2x^2+4x-10=0 | | 5x+2(x-3)=12x-5+14 | | 4(2x+3)-6x=18 | | -8x-(3x+6)=44-x | | 2t(t+5)+1=3t-3-t^2 | | 4x+4+2x= | | -3x+6=-3x+9 | | 10z+4=10(z+1)-6 | | 4i(6i)=48 | | (a-2)x=a^2-4 | | x^2-4bx+3b^2-4b-4=0 | | 2x+2x+46+x+14=180 | | -6a-15=-3a-21 | | 4x=8x+3 | | 3.2h-2.4=2.4+1.2h | | 7x+8=5x+12 | | -3[-4-(65-99)]= |